PELAKSANAAN PERJANJIAN KERJASAMA ANTARA PT. SERASI AUTORAYA DENGAN AUDI VARIASI - Siti Rafika Ilhami; Rika Lestari; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In carrying out its business, business people often forget the importance of the agreement must be made before the business was run. Most parties do business agreement orally , but some are doing the agreement in writing. Business cooperation between the parties have felt more legal certainty when held by a written agreement. Based on the understanding of the authors formulate three formulation of the problem, namely : first, the implementation of the cooperation agreement between PT. Serasi Autoraya with Audi Variasi in the provision and installation of vehicle accessories. second, the barriers that arise from the implementation of the cooperation agreement. Third, the legal consequences if the parties can not perform its obligations under the agreement .This type of research can be classified into types of socio-juridical research, because in this study the authors conducted research spaciousness. Location and population studies along with samples in this paper is on the PT. Serasi Autoraya (TRAC - Astra Rent a Car) Branches Pekanbaru with Audi Variasi. The data source consists of primary and secondary data, data collection techniques is through interviews and discussions with paraktisi field.From the research , there are three main issues that can be concluded first, Audi Variasi is not going well , because there are defaults that come from both sides. Second, barriers arise is late in payment and other obstacles are the lack of manpower which is owned by Audi Variasi, Audi Variasi facilities inadequate and the adequacy of production materials, the quality of workers to do the job. Third, the legal consequences if the parties can not perform its obligations under the agreement is the second party will be subject to compensation if mistaken in doing work. Advice, the parties should pay attention to every detail and comply with the agreed contract .Keywords: agreement, coorporation, disagreement.